2017
DOI: 10.3389/fphar.2017.00573
|View full text |Cite
|
Sign up to set email alerts
|

Alpha5 Nicotinic Acetylcholine Receptor Contributes to Nicotine-Induced Lung Cancer Development and Progression

Abstract: Nicotine and nicotinic acetylcholine receptors (nAChRs) are considered to be involved in lung cancer risk, onset and progression, but their precise physiological roles in these contexts remain unclear. Our previous studies suggested that α5-nAChR mediates nicotine-induced lung cancer cell proliferation, migration, and invasion in vitro. In this study, we aimed to determine the role of α5-nAChR in the development and progression of non-small cell lung cancer (NSCLC). Our microarray results reveal that knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 49 publications
2
36
0
1
Order By: Relevance
“…As α5-nAChR expression was observed to be associated with Jab1 expression in lung cancer patient samples, we further assessed α5-nAChR and Jab1 expressions in NSCLC xenograft tissues. As we previously reported, 17 the tumour volumes of α5-nAChR knockdown xenografts (KD) were smaller than those of the xenografts derived from control cells (NC) (Figure 2A). The immunohistochemistry assay showed that the expression of α5-nAChR and Jab1 was higher in the NC group compared to that observed in the sh-CHRNA5 tumour group ( Figure 2B).…”
Section: α5-nachr and Jab1 Expressions Are Correlated In Nsclc Tumosupporting
confidence: 78%
See 1 more Smart Citation
“…As α5-nAChR expression was observed to be associated with Jab1 expression in lung cancer patient samples, we further assessed α5-nAChR and Jab1 expressions in NSCLC xenograft tissues. As we previously reported, 17 the tumour volumes of α5-nAChR knockdown xenografts (KD) were smaller than those of the xenografts derived from control cells (NC) (Figure 2A). The immunohistochemistry assay showed that the expression of α5-nAChR and Jab1 was higher in the NC group compared to that observed in the sh-CHRNA5 tumour group ( Figure 2B).…”
Section: α5-nachr and Jab1 Expressions Are Correlated In Nsclc Tumosupporting
confidence: 78%
“…Recently, our laboratory demonstrated that α5-nAChR mediates nicotine-induced lung cancer development and progression. 17 Nicotine interacts with α5-nAChR on the cell surface, activating the JAK2/Stat3 signalling pathways and promoting lung cancer cell proliferation. 18 Furthermore, α5-nAChR mediates nicotine-induced lung cancer cell migration and invasion.…”
mentioning
confidence: 99%
“…It will be particularly insightful for at least three lung diseases where smoking may partly impact homeostasis: lung cancers, COPD, and COVID-19. (i) nAChRs single nucleotide polymorphisms (SNP) were associated to lung cancer cells [36,37] and nAChRs were shown to be involved in cancer cell proliferation and survival [38][39][40][41]. (ii) nAChRs SNPs were also associated with nicotine dependence and COPD [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the cholinergic nicotinic receptor subunit genes on chromosome 15q25.1, including CHRNA3, CHRNB4, and CHRNA5, are well-established biomarkers of chronic obstructive pulmonary disease (COPD) and lung cancer [15]. Several polymorphisms and their haplotypes in CHRNA5/CHRNA3 genes may have functional effects on (i) CHRNA5 mRNA levels, (ii) polycyclic aromatic hydrocarbon-DNA adduct levels, (iii) TP53 mutations, and (iv) susceptibility to lung cancer [16]. However, the function of the nicotinic receptor cluster on chromosome 15q25 in LAC is still unclear.…”
Section: Discussionmentioning
confidence: 99%